Four Cases of Chylous Ascites following Robotic Gynecologic Oncological Surgery - Ahmet Göçmen; Muhittin Eftal Avcı; Fatih Şanlıkan; Mustafa Gazi Uçar (Hindawi Limited, 2014)
Chylous ascites is an uncommon form of ascites characterized by milky-appearing fluid caused by blocked or disrupted lymph flow through chyle-transporting vessels. The most common causes of chylous ascites are therapeutic interventions and trauma. In this report, we present four cases of chylous ascites following robot-assisted surgery for endometrial staging and the treatment strategies that we used. After retroperitoneal lymph node dissection, leaving a drain is very useful in diagnosing chylous ascites and observing its resolution; furthermore, the use of octreotide in conjunction with TPN appears to be an efficient treatment modality for chylous ascites and should be considered before any invasive intervention.